Los derechos humanos derivados de los artículos 5 y 22 de la convención americana de derechos humanos para la evaluación del artículo 102 de la ley de migración sobre el acceso al trabajo de migrantes irregulares en tránsito. - Cruz Arizaga, Nathalie (My University, 2021)
This thesis, "LOS DERECHOS HUMANOS DERIVADOS DE LOS ARTÍCULOS 5 Y 22 DE LA CONVENCIÓN AMERICANA DE DERECHOS HUMANOS PARA LA EVALUACIÓN DEL ARTÍCULO 102 DE LA LEY DE MIGRACIÓN SOBRE EL ACCESO AL TRABAJO DE MIGRANTES IRREGULARES EN TRÁNSITO," analyzes the profound vulnerability of irregular migrants in Mexico, arguing that their lack of access to the formal labor market directly exposes them to human rights violations. The study evaluates Article 102 of Mexico's Migration Law using the standards set by Article 5 (Right to Personal Integrity) and Article 22 (Freedom of Movement and Residence) of the American Convention on Human Rights. The thesis contends that the barriers to regularization and work established in Article 102 (such as requiring a citizen sponsor) deny migrants a dignified livelihood, forcing them into exploitation, trafficking, and precarious conditions that violate their personal integrity (Art. 5). Citing Inter-American jurisprudence (like OC-18/03) which affirms labor rights regardless of migratory status , the author proposes modifying Article 102 to allow employers (physical or moral persons) to hire irregular migrants and, in doing so, provide the required sponsorship to regularize their status, thereby creating a legal pathway to employment that respects their human dignity and rights.
CAPÍTULO 1. INTRODUCCIÓN A LA MIGRACIÓN -- CAPÍTULO 2. LOS ESTÁNDARES DE LOS DERECHOS HUMANOS DE PROTECCIÓN AL MIGRANTE EN EL SISTEMA INTERAMERICANO (PARTE 1) -- CAPÍTULO 3. LOS ESTÁNDARES DE LOS DERECHOS HUMANOS DE PROTECCIÓN AL MIGRANTE EN EL SISTEMA INTERAMERICANO (PARTE 2)
Keywords: Derecho - Tesis